A Space for Collaborative Creativity. How Collective Improvising Shapes ‘a Sense of Belonging’ - Verneert, Filip; Nijs, Luc; De Baets, Thomas (Frontiers in Psychology, 2021)
In this contribution, we draw on findings from a non-formal, participatory music project to elaborate on the relationship between the concept of Eudaimonia, as defined by Seligman, the interactive dimensions of collective free improvisation and the concept of collaborative creativity. This project involves a music ensemble, TOSO (The Ostend Street Orkestra), that gathers homeless adults and people with a psychiatric or alcohol/drug related background to engage in collective musical improvisation. Between 2017 and 2019 data was collected through open interviews and video recordings of rehearsals and performances. The data from the participants were analyzed through inductive analysis based on the principles of grounded theory. An interesting finding was the discrepancy in the interviews with the participants regarding social relationships revealing some negative affect about social interaction in the group while at the same time reporting strong feelings of group coherence and belonging. Analyzing video recording of performances and rehearsals showed enjoyment and pleasure while playing the music. We assume that verbal reflection, using one to one interviews, should be complemented by the use of video recordings and analysis of moment-to moment observations in order to capture the complexity of community music projects with homeless people. We aligned the initial open coding with the 5 elements of the PERMA model. Generally speaking, we could observe more focus on Relationship (sense of belonging), Engagement (flow in rehearsals and performances and Meaning (belonging to something greater than yourself) and less on Positive Emotion and Accomplishment (goal setting).